The Influence of Flexible Working Arrangements on Turnover Intention and Productivity Through Job Satisfaction on The Millennial Generation of Private Companies in Jakarta in 2022 - Rifqi Aziz; Parwoto Parwoto; M. Ali Iqbal (International Journal of Social Service and Research, 2022)
The COVID-19 pandemic has changed the pattern of human life, work, and significant changes for companies to survive. The most obvious change is in the situation where organizational activities begin to practice flexible working arrangements or flexible working arrangements. This study aims to analyze the effect of flexible working arrangements on productivity, job satisfaction, and turnover intention through a quantitative approach and the use of the Smart-PLS 3.2.9 application with 100 millennial generation employees in Jakarta. This study shows that flexible working arrangements significantly positively affect productivity and job satisfaction. Furthermore, job satisfaction has a positive effect on productivity. However, an anomaly was found in the effect of flexible working arrangements on turnover intention, which has a significant positive relationship. This is due to the company's lack of freedom in completing its work. Job satisfaction has no significant effect on turnover intention. In the indirect effect test, it is known that job satisfaction can mediate the effect of flexible working arrangements on productivity. Moreover, job satisfaction cannot mediate between flexible working arrangements and turnover intention.